Pengembangan Produk Olahan Seaweed Sebagai Tepung Untuk Meningkatkan Nilai Ekonomi Masyarakat Di Desa Mertak, Kecamatan Pujut, Kabupaten Lombok Tengah - Wahyuningsih, Endah; Hardian, Muhamad; Hidayatullah, Muhamad Syahrul; Lestari, Fina; Kalista, Alifia Nurul (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Real Work Lectures (KKN) is one formservice of higher education institutions to the communityimplemented by Mataram University (Unram). KKN activitiesMataram University for the 2023/2024 period is a KKN activityVillage Community Empowerment (PMD) which raises the main themenamely Preanuer Village. By carrying out this theme, it is hoped that students,through the activities carried out, can contribute todevelopment and improvement of community living standards in managementproduct. One of the villages chosen as the location for implementing KKNis Mertak Village, which is in Pujut District, Lombok RegencyMiddle. In this activity, the KKN team acts as a companionpartner groups, namely the community and local governmentidentify potential and existing problems and provide solutionsfor potential development and scientifically based problem solving.The superior potential in Mertak Village is in the field of tourism,livestock, fisheries and agriculture. In the agricultural sector there are productsseaweed cultivated by the people of Mertak Village, in particularin Batu Sword Hamlet. The aim of this activity is to improveThe economic value of seaweed products to improve living standardsvillagers. This activity was carried out through field observations, teamsKKN–PMD Mertak 2 Village in developing seaweed productsinto flour will be held on December 23, 2023 – 06February 2024 or as long as KKN activities take place, located in HamletBatu Sword, Mertak Village, Pujut District, Central Lombok Regency.Service activities of the Unram KKN–PMD team which have been carried out inMertak Village is designed to help the community improveeconomic value of seaweed products. Results obtained from activitiesthis is the knowledge and skills of the community in managing andprocessing seaweed products.